Pendampingan Manajemen Usaha Perempuan Pascabencana Banjir Bandang di Desa Huta Godang untuk Penguatan Ekonomi Lokal - Nurdelila; Rizky Mery Octavianna Lubis; Yusuf Pathuansyah; Mahrani (Yayasan Perguruan Kampus, 2026)
The flash floods that struck Huta Godang Village significantly impacted the sustainability of community micro-enterprises, particularly women who were economically vulnerable after the disaster. This community service activity aimed to improve the business management capacity of women affected by the flash floods as a strategy for local economic recovery and strengthening. The approach used was participatory, empowerment-based mentoring through business management training and mentoring, covering business planning, simple financial management, and marketing strategies. The program targeted women micro-enterprises and female heads of households in Huta Godang Village. The program evaluated participants' pre- and post-mentoring conditions using descriptive statistical data. The results showed a significant increase in participants' managerial capacity, indicated by an increase in the proportion of participants who had business plans, maintained financial records, and implemented simple marketing strategies. Furthermore, some participants began to experience a gradual recovery in their business income and demonstrated increased economic independence. This activity demonstrated the effectiveness of post-disaster mentoring for women's business management in supporting community economic recovery and strengthening women's roles as actors in local economic development. Therefore, this mentoring model has the potential to be replicated in other disaster-affected areas with similar social and economic characteristics